2013
DOI: 10.1007/s13204-013-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural, optical and ferroelectric properties of V doped ZnO

Abstract: Present work reports the structural, optical and ferroelectric properties of vanadium doped ZnO samples synthesized via solid state reaction method. X-ray diffraction (XRD) study confirms the presence of hexagonal wurtzite phase and the slight changes in lattice parameters is observed after V doping in host ZnO and impurity oxide of ZnV 2 O 6 . Presence of E 1 and E 2 modes in Raman spectroscopy of V doped ZnO indicates the stability of the wurtzite structure of ZnO, which is consistent with the XRD results. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…They showed that the lattice constant “a” in zinc oxide remains constant while ‘c’ decreases with increasing vanadium. However, our results are in conflict with previous observations by Joshi et al., which reported an increase in the lattice parameter with adding vanadium to ZnO lattice. These discrepancies may be attributed to oxidation states of vanadium (2, 3, 4 or 5) which is substituted in the lattice of zinc oxide.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…They showed that the lattice constant “a” in zinc oxide remains constant while ‘c’ decreases with increasing vanadium. However, our results are in conflict with previous observations by Joshi et al., which reported an increase in the lattice parameter with adding vanadium to ZnO lattice. These discrepancies may be attributed to oxidation states of vanadium (2, 3, 4 or 5) which is substituted in the lattice of zinc oxide.…”
Section: Resultscontrasting
confidence: 99%
“…It was reported that the method of synthesis and preparation has an important effect on the morphology, homogeneity, photocatalytic performance, and sinterability of ceramic powders . Some approaches for synthesizing V‐doped ZnO particles and ZnO‐V 2 O 5 composites have been proposed including solid‐state reaction, sol‐gel, co‐precipitation method, decomposition method, etc. To the best of our knowledge, a study focused on the preparation of V‐doped ZnO via microemulsion method and its photocatalytic properties has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the figure, seven major peaks are seen at 31.8°, 34.5°, 36.3°, 47.5°, 56.7°, 62.9°, and 68° which can be consigned to diffraction from (100), (002), (101), (102), (110), (103), and (112) planes respectively for a lattice constant of a = b = 3.24 Å and c = 5.2066 Å [38]. The XRD pattern clearly reflects the presence of the hexagonal wurtzite phase crystal structure for pure ZnO nanoparticles (JCPDS: 36-1451) [39].…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 315 cm −1 could be attributed to triply coordinated oxygen (V 3 -O) bond and stretching band [52]. There are many modes in the wave number range of 750-1000 cm −1 arises due to different oxidation states of vanadium [6,16].…”
Section: Ftir Spectroscopymentioning
confidence: 99%